Pelaksanaan Kurikulum Merdeka di SAM Negeri 10 Palembang - Putri, Helmalia; Astuti, Mardiah; Hidayat, Hidayat (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research aims to determine the implementation of the independent curriculum at SMA Negeri 10 Palembang. The type of research is qualitative. The study is conducted using a qualitative descriptive approach, and data collection methods include interviews, observations, and documentation. The data analysis techniques employed in this research are data reduction, data presentation, conclusion drawing, and triangulation. The results indicate that the implementation of the independent curriculum at SMA Negeri 10 Palembang is relatively good. This is evident from the activities of providing instructions, coordination, motivation, and guidance carried out by the school principal to achieve the goals of implementing the independent curriculum. Supporting factors for the implementation of the independent curriculum at SMA Negeri 10 Palembang include the role of teachers, student motivation, and effective planning in the availability of learning resources. However, inhibiting factors include the uneven role of teachers and access to learning resources.